SISTEM PENGELOLAAN KEUANGAN KERTAS BERBASIS IOT PADA KOTAK AMAL MASJID - Priyandi, Priyandi; Trimedya Oktama, Sudewa; Saputra, Zanu; Meliya Ningsih, Riski (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The management of paper money in mosque donation boxes has been done manually, which can lead to delays in recording and the risk of discrepancies in the amount of money. To address this issue, an Internet of Things (IoT) based system has been designed that can automatically count, record, and monitor the incoming paper money in the donation box. This system aims to facilitate the mosque committee in managing incoming funds more efficiently, transparently, and accountably. This system uses several key components such as a paper money detection sensor, a microcontroller, a solenoid to control the mechanism for money entry, an LCD screen to display the nominal amount, and IoT connectivity for real-time data transmission. When money is inserted, the sensor will read the nominal amount, activate the solenoid to direct the money to the storage, and automatically record the transaction data. This information is then sent.